2015
DOI: 10.1007/s13398-015-0255-1
|View full text |Cite
|
Sign up to set email alerts
|

On k-quasi- $$*$$ ∗ -paranormal operators

Abstract: For a positive integer k, an operator T ∈ B(H ) is called k-quasi- * -paranormal if T * T k x 2 ≤ T k x T k+2 x for all x ∈ H , which is a common generalization of * -paranormal and quasi- * -paranormal. In this paper, firstly we prove some inequalities of this class of operators; secondly we give a necessary and sufficient condition for T to be kquasi- * -paranormal. Using these results, we prove that: (1) if T * T n = T n T for some positive integer n ≥ k, then a k-quasi- * -paranormal operator T is normaloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In [16], Stampfli showed that if T satisfies the growth condition G 1 , then E is self-adjoint and R(E) = ker(T − µ). Recently, Jeon and Kim [11], Uchiyama [18] and Rashid [15] obtained Stampfli's result for quasi-class A operators, paranormal operators and k-quasi- * -paranormal operators. In general even if T is a paranormal operator, the Riesz idempotent E of T with respect to µ is not necessarily self-adjoint.…”
Section: Riesz Idempotent For K-quasi-class a N Operatorsmentioning
confidence: 98%
“…In [16], Stampfli showed that if T satisfies the growth condition G 1 , then E is self-adjoint and R(E) = ker(T − µ). Recently, Jeon and Kim [11], Uchiyama [18] and Rashid [15] obtained Stampfli's result for quasi-class A operators, paranormal operators and k-quasi- * -paranormal operators. In general even if T is a paranormal operator, the Riesz idempotent E of T with respect to µ is not necessarily self-adjoint.…”
Section: Riesz Idempotent For K-quasi-class a N Operatorsmentioning
confidence: 98%
“…This class of operators introduced and studied by K. Tanahashi and A. Uchiyama. The references [12,13,14] are among the various extensions of these classes of operators.…”
Section: Introductionmentioning
confidence: 99%